The social significances, the institutions and social order. Theoretical notes - Balsamo Fasce, Larissa (2007)
In order to allow the society exists as such, human being must be brought under a socialization process through the institutions the society has introduced him since his birth. These institutions are represented primarily by the mother. The constitution of every society and its characteristics are very particular in every case. What “shapes” a society and makes it different from others is a series of elements called imaginary social significances which are out of the power of perception, and are constantly transforming, nourishing and being at the same time cause of a tight relation between person and society. In this relationship both of them depend on the institutions to structure and perpetuate.